Effect of physical activity based on traditional games on the psychological well-being of elementary school children. - Dennys Christovel Dese; Arthur Huwae; Panji Arvino Putra Nugraha (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
A holistic learning program is essential to provide high-quality human resources (HR) in the education system. An optimal human resource is attained through a healthy child development process physically and psychologically. Children will experience physical, cognitive, emotional, and psychosocial changes or the child development phase. This study aims to identify the effect of traditional game-based physical activities on the psychological well-being of elementary school children at MI Sabilul Huda Jimbaran. The qualitative experimental method, particularly a one-group pretest-posttest design, was applied as the research design. Moreover, the research instrument employed the questionnaire by purposively involving 80 students selected from fourth and fifth grade. They were the students of MI Sabilul Huda Jimbaran. This study's data analysis covers validity, reliability, normality, and hypothesis tests. The results indicated that physical activities based on traditional games significantly affect elementary school children's psychological well-being. Keywords: traditional games, psychological well-being, elementary school students